Diversification of Higher Education in Vietnam: Experiences in International Cooperation and Financial Autonomy at the VNU-International School - Do, Nguyễn Trọng; Lập, Ngô Tự (VNU Journal of Science: Education Research; Vol 32 No 1, 2016)
Abstract Since 1986, the beginning ofVietnam’s Renovation Policy (Đổi mới), the Vietnamese educational system has undergone multiple reforms directed toward meeting the demands of society in terms of volume, quality and international values. This renovation process is currently facing many difficulties and challenges, the most critical of which concerns financial security in the context of a relatively weak economy. Based on an analysis of different mutations of higher education (HE) in the world and on the experiences of the International School, Vietnam National University, Hanoi (VNU-IS), this article tries to show that the diversification of financial resources through “socialization" and internationalization is a feasible and even optimal solution for producing resources allowing Vietnamese post-secondary education to achieve and maintain international standards. Received 02 October 2015; Revised 26 November 2015; Accepted 25 March 2016 Keywords: Financial management, Internationalization of higher education, joint program, International School.